2023
DOI: 10.1002/mco2.323
|View full text |Cite
|
Sign up to set email alerts
|

The recent progress of myeloid‐derived suppressor cell and its targeted therapies in cancers

Abstract: Myeloid‐derived suppressor cells (MDSCs) are an immature group of myeloid‐derived cells generated from myeloid cell precursors in the bone marrow. MDSCs appear almost exclusively in pathological conditions, such as tumor progression and various inflammatory diseases. The leading function of MDSCs is their immunosuppressive ability, which plays a crucial role in tumor progression and metastasis through their immunosuppressive effects. Since MDSCs have specific molecular features, and only a tiny amount exists i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 299 publications
0
2
0
Order By: Relevance
“…Delving further, there are prospective avenues yet to be explored, suggesting potential interventions based on the observed TIME heterogeneity across different molecular subtypes of TNBC. In the case of LAR tumors, MDSC-targeted therapies could be of potential value, including inhibition of MDSC function or recruitment into the TIME, inducing their differentiation or mediating their depletion [ 56 , 57 ]. In patients with the MSL subtype, featuring a high number of M2 TAMs, inhibition of the chemokine (C-C motif) ligand 2 (CCL2)/circulating chemokine-receptor-type 2 (CCR2) axis could decrease the recruitment of bone marrow mononuclear cells, subsequently reducing macrophage infiltration in the breast [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Delving further, there are prospective avenues yet to be explored, suggesting potential interventions based on the observed TIME heterogeneity across different molecular subtypes of TNBC. In the case of LAR tumors, MDSC-targeted therapies could be of potential value, including inhibition of MDSC function or recruitment into the TIME, inducing their differentiation or mediating their depletion [ 56 , 57 ]. In patients with the MSL subtype, featuring a high number of M2 TAMs, inhibition of the chemokine (C-C motif) ligand 2 (CCL2)/circulating chemokine-receptor-type 2 (CCR2) axis could decrease the recruitment of bone marrow mononuclear cells, subsequently reducing macrophage infiltration in the breast [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Myeloid Derived Suppressor Cells (MDSCs) represent a heterogeneous population of immature myeloid cells characterized by the cell surface markers CD11b and Gr1 (Ly6G/Ly6C) in mouse and by HLA-DR-, CD11b, CD14/15 and more in human (12)(13). Notably, MDSCs have emerged as critical immune regulators in various contexts including cancer and other developmental processes such as wound healing, placenta formation, and more (14)(15)(16)(17)(18)(19)(20)(21)(22)(23). We have previously showed that MDSCs play key roles in the early stages of liver regeneration.…”
Section: Introductionmentioning
confidence: 99%